PENINGKATAN KOMPETENSI GURU DALAM PEMBELAJARAN DIFFERENSIASI DENGAN KOMUNITAS BELAJAR SD KALONGAN 03 - Adliroh; Ari Teliti Wilarsati; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The problem faced by partners is the lack of innovation in designing learning in the classroom so that it seems boring and monotonous. This can have an impact on students' interest and motivation in participating in learning. So there is a need to increase teachers' creativity and innovation in designing learning, especially designing learning that is tailored to the needs of students. Therefore, teacher competency development is designed through the Learning Community. The purpose of this activity is to improve teachers' competence in designing differentiated learning based on the sharing of experience and knowledge among fellow educators. The teacher behavior experienced by students after the KomBel training showed that most of the teachers had shown a medium category, namely 5 teachers (45.6%), and there were 5 teachers (45.6%) who had shown a high category. Meanwhile, those who are still in the low category are 1 teacher (8.8%). This shows that there has been an increase in teacher behavior after being given training through KomBel.